The gravity of cross-border R&D expenditure - Sandra Leitner; Bernhard Dachs; Robert Stehrer (European Regional Science Association (ERSA), 2012)
In recent years, firms have considerably decentralized their research and development (R&D) activities. Subsidiaries of foreign multinational enterprises (MNEs) are now among the top performers of R&D in many EU and non-EU countries. Specifically, MNE affiliates account for around 20% of total business R&D in France, Germany and Italy; between 30% and 50% in Canada, Portugal, the Slovak Republic, Sweden and the United Kingdom; and more than 50% in Austria, Belgium, the Czech Republic, Hungary and Ireland. Against that backdrop, the paper uses a novel and unique data base on R&D expenditure of foreign-owned firms for a set of OECD countries and identifies and analyzes factors that drive the scale of R&D expenditure across countries and sectors. The empirical analysis employs a gravity approach which demonstrates that geography plays a pivotal role as distance between host and home country of a foreign-owned firm, a common language spoken in both home and host countries, or common borders are key drivers of cross-border R&D investments. Moreover, results reveal that additional determinants such as larger host and home country markets or superior host country human capital bases are conducive to R&D expenditure of foreign-owned firms while stronger human capital bases in home countries deter R&D efforts of foreign-owned firms abroad.
Keywords: F23; O32; O33; 330; internationalisation of research and development; multinational firms; gravity model